Readmission after inferior vena cava filter placement for acute venous thromboembolism in the United States: Impact of a cancer diagnosis. Issue 9 (22nd July 2020) - Guha, Avirup; Dey, Amit K.; McKinley, Grant; Carter, Rebecca R.; Miller, P. Elliott; Deshmukh, Abhishek J.; Zaghlol, Raja; Barac, Ana; Desai, Nihar R.; Addison, Daniel
Abstract: Background: Inferior vena cava filter (IVCF) use is common after a venous thromboembolic event (VTE). Cancer is associated with higher rates of VTEs and is also seen in a significant proportion of patients requiring IVCF. As hospital readmissions remain a frequently scrutinized metric, we sought to evaluate the impact of cancer on hospital‐readmission rates and in‐hospital outcomes among patients with VTEs who received an IVCF. Methods: Leveraging the 2013 to 2014 Nationwide Readmission Database, we identified adult patients presenting with a VTE in the United States and evaluated 30‐day readmission rates and readmission in‐hospital outcomes postindex‐admission. Multivariable logistic regression was used to identify factors associated with readmission after an index‐procedure, including traditional and nontraditional cardiovascular risk factors, as well as hospital‐level characteristics. Results: Among the 619 241 patients presenting with a VTE at index‐admission, 11.2% of patients received IVCF on index‐admission, of which 30.9% had cancer. The 30‐day readmission rate amongst IVCF recipients was 15.8% (N = 10 927), and 19.9% amongst those with cancer compared to 13.9% in patients without cancer ( P  < .001). Moreover, cancer patients had longer lengths of stay in the hospital (4.5 ± 0.2 vs 4.0 ± 0.1 days; P  = .02), higher cost of care ($10 900 ± 308 vs $9242 ± 206; P  = .007), but no difference in mortality (8.3% vs 6.3%; P  = .70) during readmission compared to noncancer patients. Conclusion: Readmission after IVCF placement is common. In patients readmitted after an IVCF implantation, those with cancer have longer hospital stays and higher costs of care. However, in‐hospital mortality is similar to those without cancer.